Proceedings of the 12th ACM Workshop on Workshop on Privacy in the Electronic Society 2013
DOI: 10.1145/2517840.2517844
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of data granularity on privacy for the smart grid

Abstract: The upgrade of the electricity network to the "smart grid" has been intensified in the last years. The new automated devices being deployed gather large quantities of data that offer promises of a more resilient grid but also raise privacy concerns among customers and energy distributors.In this paper, we focus on the energy consumption traces that smart meters generate and especially on the risk of being able to identify individual customers given a large dataset of these traces. This is a question raised in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Thus, in terms of privacy, it is not so significant. Moreover, such noisy data can also discourage re-identification attacks, such as the one discussed in [24], which attempts to find mappings between non-identifiable, high-frequency energy usage data and identifiable, low-frequency data.…”
Section: Privacy Preservation By Added Noisementioning
confidence: 99%
“…Thus, in terms of privacy, it is not so significant. Moreover, such noisy data can also discourage re-identification attacks, such as the one discussed in [24], which attempts to find mappings between non-identifiable, high-frequency energy usage data and identifiable, low-frequency data.…”
Section: Privacy Preservation By Added Noisementioning
confidence: 99%
“…These types of data are called HighFrequency data (HF data) [4] and as mentioned earlier, raise privacy concerns. In earlier work [12] we show that even if the HF data is anonymized, an adversary can successfully link such an HF dataset with the corresponding LF dataset to identify a large portion of the households.…”
Section: Introductionmentioning
confidence: 97%
“…In the case of data from the AMI, previous research has shown that only a portion of the households' identities are protected, i.e. cannot be re-identified, as smart metering data characteristics can be used in the de-pseudonymization process [1,7,12]. However, it is important to better understand the conditions under which the suggested de-anonymization process works and how the number of protected households change given properties of the dataset obtained by the adversary.…”
Section: Introductionmentioning
confidence: 99%
“…Tudor et al [2] showed that when the two datasets (training and testing) contain consumption traces from the same period of time, re-identifying consumers is trivial by looking at the total electricity consumption of each trace. Most of the work in this space (including ours) assumes that training (the dataset with identifiers) and testing (the anonymized dataset) contain electricity consumption samples that are non-overlapping in time [3], [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%